Impact of ion irradiation, elemental doping and coating cycles on structural characteristic parameters of nanocrystalline VO2 thin films - Khan, G.R (Micro & nano letters, 2020)
The origin of the structural phase transition in vanadium dioxide (VO2) has been the subject of immense disagreement in spite of decades of research carried out to comprehend this intriguing phenomenon. Diverse models have been developed to elucidate the obscure theory in order to corroborate assorted experimental results. Herein, the influence of swift heavy ion irradiation, elemental doping and coating cycles on the structural properties of thin films synthesised by sol–gel technique and deposited by spin coater on alumina and glass substrates is investigated. The thin films were characterised by X-ray diffractometry and the XRD spectra obtained at 1E11, 5E11, 1E12 ion beam fluances of 200 MeV Ag9+-ion irradiation; at 1, 3, 5% of Mo6+-ion doping and at different spin coating cycles were analysed to probe the influence of these effects on the structural characteristic parameters of nanocrystallites in VO2 thin films. This aspect of VO2 thin films has not been investigated to its full capacity and consequently, not reported in the scientific literature.